Effects of temperature and Saccharomyces cerevisiae co-culture on mycotoxins stability and decontamination in wheat - Khurram Abbas; Usama; Javed Abbas; Muhammad Imran (Nutrimentum et Curae)
Mycotoxins found in cereals have adverse effects on animals, humans, and agricultural products, posing significant health risks and affecting the marketability of wheat products.